Pengaruh umur, pendidikan, upah, keterampilan, dan jenis kelamin terhadap lama mencari kerja bagi pekerja terdidik di Kota Jambi (studi kasus Kecamatan Kota Baru dan Telanaipura) - Cici Swarsih; Junaidi Junaidi; Rosmeli Rosmeli (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2020)
This study aims to analyze the characteristics of educated workforce and to determine the effect of variables of age, education, wage level, skills and gender on duration of looking for work by educated worker in Jambi City. The data used in this study are primary data obtained from questionnaires and direct interviews with a total sample of 110 respondents. Sampling in this study uses a multistage sampling method that is sampling in stages. Data analysis methods used are descriptive and quantitative analysis. The analytical tool used is the OLS (Ordinary Least Square) method. The results of this study indicate that the independent variables simultaneously have a significant effect on duration of looking for work. Partially the variables of age, education, wage level have a significant effect on duration of looking for work, while the skills and gender variables have no significant effect on the duration of looking for work.